THE EVOLVING COMPETENCIES OF THE PUBLIC AUDITOR AND THE FUTURE OF PUBLIC SECTOR AUDITING - Aslan, Lale (EMERALD GROUP PUBLISHING LTD, 2021)
The protection of public assets, fighting corruption and providing accountability for government agencies is necessary for public welfare, and it is possible to achieve this by quality auditing of the public sector. Since audit quality depends on the competencies of the auditor, this chapter focusses on the competencies of the public auditor and how these competencies are expected to evolve in the future with the development of technology. The chapter concentrates on the most sought-after skills for today's public auditors by analysing the employment criteria in the Supreme Audit Institutions (SAIs) of the European Union, the United States, the United Kingdom and Turkey. Even though the SAIs of these countries/regions are quite different, it is possible to find common ground. The SAIs of these countries, in general, require public auditors to have an undergraduate degree and require the candidates to pass extensive tests on reasoning abilities. Moreover, the author investigates the requirements for public auditor competency in the public auditing standards followed by these countries. In addition to this, the author discusses the future expectations from public auditors and the new skills these will need. Past skills include technical knowledge, prior experience, hierarchical order in audit teams, professional scepticism, reasoning abilities and reporting skills. Advancements in technology such as Artificial Intelligence and Industry 4.0 will require auditors to have technological knowledge, emotional intelligence, interpersonal skills, project management skills, critical thinking and strong communication skills. Furthermore, understanding the business and related risks will overshadow prior experience.
Keywords: Auditor skills; auditor competency; supreme audit institutions; Industry 4.0; compliance; regulation; ACCOUNTABILITY; Business & Economics; Public Administration